MAGMATIC EVOLUTION AND ASCENT HISTORY OF THE ARIES MICACEOUS KIMBERLITE, CENTRAL KIMBERLEY BASIN, WESTERN AUSTRALIA: EVIDENCE FROM ZONED PHLOGOPITE PHENOCRYSTS, AND UV LASER 40AR/39AR ANALYSIS OF PHLOGOPITE-BIOTITE - Downes P.J.; Wartho Jo.A.; Griffin B.J. (My University, 2006)
The Neoproterozoic Aries kimberlite was emplaced in the central Kimberley Basin, Western Australia, as a N–NNE-trending series of three diatremes infilled by lithic-rich kimberlite breccias. The breccias are intruded by hypabyssal macrocrystic phlogopite kimberlite dykes that exhibit differentiation to a minor, high-Na–Si, olivine–phlogopite–richterite kimberlite, and late-stage macrocrystic serpentine–diopside ultramafic dykes. Mineralogical and geochemical evidence suggests that the high-Na–Si, olivine–phlogopite–richterite kimberlite was derived from the macrocrystic phlogopite kimberlite as a residual liquid following extended phlogopite crystallization and the assimilation of country rock sandstone, and that the macrocrystic serpentine–diopside ultramafic dykes formed as mafic cumulates from a macrocrystic phlogopite kimberlite. Chemical zonation of phlogopite–biotite phenocrysts indicates a complex magmatic history for the Aries kimberlite, with the early inheritance of a range of high-Ti phlogopite–biotite xenocrysts from metasomatized mantle lithologies, followed by the crystallization of a population of high-Cr phlogopite phenocrysts within the spinel facies lithospheric mantle. A further one to two phlogopite–biotite overgrowth rims of distinct composition formed on the phlogopite phenocrysts at higher levels during ascent to the surface. Ultra-violet laser 40Ar/39Ar dating of mica grain rims yielded a kimberlite eruption age of 815·4?±?4·3?Ma (95% confidence). 40Ar/39Ar laser profiling of one high-Ti phlogopite-biotite macrocryst revealed a radiogenic 40Ar diffusive loss profile, from which a kimberlite magma ascent duration from the spinel facies lithospheric mantle was estimated (assuming an average kimberlite magma temperature of 1000°C), yielding a value of ?0·23–2·32?days for the north extension lobe of the Aries kimberlite.
Keywords: 40Ar/39Ar; diamond; kimberlite; mantle metasomatism; phlogopite–biotite; Докембрий::Протерозой::Неопротерозойская; Precambrian::Proterozoic::Neoproterozoic